Ownership Structure and Bank Performance - Abdul Rahman, Nora Azureen; Md Reja, Anis Farida (2015)
This paper provides evidence on the impact of different types of ownership structure on bank performance.Using secondary data, the empirical analysis of this study is confined to Malaysian commercial banks during the period of 2000 to 2011. Multiple regression with fixed effects model is used to test the research model.Testing on five categories of ownership structure such as insider, family, government, institutional and foreign ownership, the results suggest that bank performance varies with different types of ownership structure.